Quality Tests of Commercial Gefarnate Fine Granules and Granule - HOTATE, TAKAKO; HARADA, AKO; NARUI, REIKO; TANAKA, KUMIKO; ISHIKURA, CHIYOJI; MAEDA, MASAKI; INOUE, CHIKAKO (Byōin yakugaku, 1984)
Quality tests were made on 10 different commercial gefarnate preparations in fine granules as well as granule, which are drugs for gastric or duodenal ulcer. The availability in handling was evaluated on each preparation by examinations of physical properties, such as angle of repose, loose bulk density, packed bulk density, dispersibility and particle size distribution. The stability was also examined by measuring content, hydrolysis rate, peroxide value, because gefarnate is the ester of geraniol and farnecyl acetate of isoprene structure. In addition study was done on the relation between the results of the examinations and the methods of granulation. From the results of the physical property tests, all the preparations were within acceptable range in actual dispensing. But in 4 preparations out of 10, the amount of gefarnate decreased on the measurement of the content. Peroxide values of these preparations were remarkably high, whereas hydrolysis rate indicated no significant value when these were compared with other commercial preparations. Therefore, it is concluded that degradation process was mainly due to the oxidation. These 4 preparations were produced by extruding granulation procedure. Gefarnate is degraded easily, and its preparations may show great difference in pharmaceutical quality when produced in different techniques.